Usaha Mebel Yumna Sofa di Desa Padang Mekar Kecamatan Padangguni Kabupaten Konawe - Leni Saleh; Riana Nur Fadilla; Rian Andika Putra; Nuryanti Nuryanti; Juliana Eka Putry; Nasmuddin Nasmuddin (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This community service (PKM) uses a participatory approach from partners (participatory approach) so that partners are involved starting from identifying problems, selecting solutions. The "Yumna Sofa" business has been running since 2018, producing Sofas and Tables. The number of workers is five (5) people. The problems experienced by the "Yumna Sofa" business are business management, production and marketing. The products produced are Sofas and tables, and chairs. The raw wood materials are quite available, it's just that there is no standardization of wood quality. The activity was held in two stages, namely the PKM KKN Posko I Team survey on Saturday, September 30, 2024 and the Community Service (PKM) KKN Posko I Team discussion on Wednesday, October 9, 2024 at Mr. Muhdi's residence. The PKM activity has been successfully implemented by applying a participatory approach method to the "Yumna Sofa" business. Participatory methods used include monitoring, lecture methods and discussions to provide solutions faced by business partners including how to improve the quality of raw materials, more patterned and quality products, business management and digital marketing in increasing sales of the products offered.